FOREIGN EXPERIENCE OF TOP MANAGEMENT TEAMS AND INTERNATIONAL DIVERSIFICATION STRATEGIES OF U.S. MULTINATIONAL CORPORATIONS - SAMBHARYA, RAKESH B. (Strategic Management Journal, 1996)
This paper extends upper echelon theory to the international business arena and tests the hypothesis that the foreign experience of top management team (TMT) members is associated with international diversification strategies. Regression analyses indicate that TMTs with a higher mean, greater heterogeneity, and a higher proportion of managers with foreign experience in 54 U.S. multinational corporations were significantly associated with the firm's international involvement.